The Consumer Protection Act 1999: 10 years after - Amin, Naemah (2011)
15th November 2009 marked the tenth anniversary of the Consumer Protection Act 1999 (the CPA), which was introduced with the noble idea of providing better protection to consumers in Malaysia. The CPA covers all the main areas of consumer protection such as supply of goods, supply of services, product safety and liability and redress mechanism. The Act provides civil remedies for aggrieved consumers and criminal sanctions for breaking its relevant provisions. Nonetheless what was seen as an important step forward for consumer rights has a low profile and seems to be underutilized. For example, the CPA has produced not a single reported case on civil liability for defective product which requires proceeding in the ordinary court. The question thus arises as to the effectiveness of the legal principles provided under the CPA in protecting the consumers. This paper aims to examine the extent to which the CPA has improved the position of consumers in Malaysia for the past 10 years. All major amendment to the CPA, the Regulations and Orders made under it will be analysed. Under the CPA, the Tribunal for Consumer Claims was set up to provide speedy, inexpensive and informal redress of consumers’ grievances. The paper analyses the developments and effectiveness of the Tribunal in achieving its function. The effectiveness of enforcement of penal sections of the Act will also be discussed. The paper finally considers the future development of the CPA and makes recommendations for the betterment of consumer protection in Malaysia.